âPEDULI DAN BERBAGIâ Strategi Peningkatan Keuntungan PT. Indocement Tunggal Prakarsa Tbk. Plant Palimanan Melalui Pelaksanaan Corporate Social Responsibility - , Kristian Hendra Permana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT. Indocement Tunggal Prakarsa, Tbk. Plant Palimanan Cirebon is one of extractive based-companies that operate in cement industry. In company operational which has achieved more than three decades, Indocement has experienced various matters regarding to its surroundings. Society protest due to mining activity, occupation demand, illegal area occupancy, etc., is a part of experiences had been around by the company. Realizing the position, management division of Indocement from beginning has designed company social responsibility implementation scheme to the environment surrounding the operating area. The scheme is operated step by step, starting from charity scheme that only involves âfire extinguisherâ to community development that is ongoing oriented. A question appears, actually what encourages the company to do this social responsibility. Indeed, there is certain motive underlying it. Finally the researcher concludes that moral duty to do something useful to the community surrounding the company becomes main motive of Indocement to perform the CSR programs. The research done in area of PT. Indocement Tunggal Prakarsa, Tbk. Plant Palimanan Cirebon particularly in Blok Kebon Gedang Desa Ciwaringin is performed with participative qualitative method. Here, the researcher participates in the CSR section staffsâ daily task, while seeing through the daily life of Blok Kebon Gedang Batik makers, a place in which Kampung Batik Ciwaringin program performed. Implementation of Kampung Batik Ciwaringin program truly shows seriousness of Indocement in performing Corporate Social Responsibility. On the other side, the company motivation to get more profit by performing CSR actually takes imperative role at implementing program they are performing. The motivation then is called by GMO Plant Palimanan as Care Share Relation. It means that the company as a part of community needs to always care and share with the environment. Indocement views at this matter not as a duty, but truly their need to achieve production sustainability.